Inovasi Biopori Sebagai Solusi Genangan Air di Desa Waelawi, Kecamatan Malngke Barat, Kabupaten Luwu Utara: Biopori: Solusi Cerdas Mengatasi Genangan Air dengan Resapan Alami - Kristopel Hutasoit; Sunrixon Carmando Yuansah (Departemen Teknologi Pertanian Universitas Hasanuddin, 2026)
Flooding is a natural disaster that frequently occurs in Waelawi Village. Biopori Infiltration Holes offer a practical solution to this problem. This community service activity aimed to socialize the concept of biopori infiltration holes and their application within the community. In addition to increasing the soil's water absorption capacity, the application of biopori infiltration holes can also enhance soil fertility. The methods used included delivering informational material and conducting a direct demonstration of how to apply the biopori infiltration holes. The activity results showed a high level of enthusiasm from the community. Participants of the socialization expressed their willingness to try and independently implement this biopori innovation. Through this program, a total of 4 biopori pipes were successfully installed in Waelawi Village, each with specifications of approximately ±70 cm in length and 3 inches in diameter per unit. Thus, this activity contributed to raising community awareness in managing water stagnation as a step to minimize the risk of flood disasters.